Car plate detection using machine learning techniques - Ang, Tian Hao (Nanyang Technological University, 2021)
With technological advancement, the use of Automatic Number Plate Recognition (ANPR) system to detect vehicle license plate has increased. The ANPR system makes use of object detection and text recognition to achieve this aim.